ANALISIS KECURANGAN LAPORAN KEUANGAN DENGAN MENGGUNAKAN FRAUD TRIANGLE (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2018-2020) - A’idatul Khoir; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This observe pursuits to decide the impact of possibilities, pressures, and explanation (the fraud triangle) on fraudulent economic reporting. The research approach used is a quantitative associative observe through reading facts on production businesses listed at the Indonesian inventory change (IDX) in 2018-2020. The studies pattern become conducted by way of a centered sampling method with several criteria defined with the aid of the researcher, in order that the studies sample became obtained from 35 production companies. statistics analysis was carried out using descriptive statistical methods, normality tests, classical assumption checks, speculation checking out, and more than one linear checks using SPSS. The results confirmed that a few and large opportunities, pressures and rationalizations had a great fantastic effect on fraud with financial statements, as evidenced by using the calculation of > table t and sig. 0.05. The value of R square is 0.920, so the level of influence between the independent variables and the structured used is 92.0%, and the rest is stricken by different variables.Keywords: Fraud Triangle, Fraudulent Financial Statements, Indonesia Stock Exchange (IDX)